The impact of nanoparticle-driven lysosomal alkalinization on cellular functionality - Bella B. Manshian; Suman Pokhrel; Lutz Mädler; Stefaan J. Soenen (Journal of Nanobiotechnology, 2018)
Abstract Background The biomedical use of nanosized materials is rapidly gaining interest, which drives the quest to elucidate the behavior of nanoparticles (NPs) in a biological environment. Apart from causing direct cell death, NPs can affect cellular wellbeing through a wide range of more subtle processes that are often overlooked. Here, we aimed to study the effect of two biomedically interesting NP types on cellular wellbeing. Results In the present work, gold and SiO2 NPs of similar size and surface charge are used and their interactions with cultured cells is studied. Initial screening shows that at subcytotoxic conditions gold NPs induces cytoskeletal aberrations while SiO2 NPs do not. However, these transformations are only transient. In-depth investigation reveals that Au NPs reduce lysosomal activity by alkalinization of the lysosomal lumen. This leads to an accumulation of autophagosomes, resulting in a reduced cellular degradative capacity and less efficient clearance of damaged mitochondria. The autophagosome accumulation induces Rac and Cdc42 activity, and at a later stage activates RhoA. These transient cellular changes also affect cell functionality, where Au NP-labelled cells display significantly impeded cell migration and invasion. Conclusions These data highlight the importance of in-depth understanding of bio-nano interactions to elucidate how one biological parameter (impact on cellular degradation) can induce a cascade of different effects that may have significant implications on the further use of labeled cells.